2023
DOI: 10.1021/jacs.3c07748
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Coacervate Protocells with Cytoprotective Metal–Phenolic Network Membranes

Linli Jiang,
Yiwei Zeng,
Hui Li
et al.

Abstract: Protocells have garnered considerable attention from cell biologists, materials scientists, and synthetic biologists. Phaseseparating coacervate microdroplets have emerged as a promising cytomimetic model because they can internalize and concentrate components from dilute surrounding environments. However, the membrane-free nature of such coacervates leads to coalescence into a bulk phase, a phenomenon that is not representative of the cells they are designed to mimic. Herein, we develop a membranized peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Au@MPN was prepared using a one-pot method according to our previous description . Specifically, 20 μL of 50 nm AuNPs, 20 μL of 10 mg mL –1 TA, and 20 μL of 2 mg mL –1 SrCl 2 were added into 400 μL of H 2 O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Au@MPN was prepared using a one-pot method according to our previous description . Specifically, 20 μL of 50 nm AuNPs, 20 μL of 10 mg mL –1 TA, and 20 μL of 2 mg mL –1 SrCl 2 were added into 400 μL of H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Metal–phenolic networks (MPNs) are amorphous metal–organic frameworks (MOFs) formed by polyphenols and metal ions, which are synthesized in mild conditions with simple steps, , avoiding toxic precursors and solvents as well as harsh conditions . The rapid coordination kinetics and unique adhesive nature of MPNs allow it to function as a coating .…”
Section: Introductionmentioning
confidence: 99%
“…However, the stability of these membranes is highly sensitive to environmental changes such as ionic strength, which could pose challenges in maintaining the desired state of the droplets. Given that the lipid membranes are sensitive to environmental changes, metal-organic systems with enhanced stability have been used to membranize coacervate droplets 38 . Polyphenols coordinate with metal ions can form the metal–phenolic networks (MPNs) that can fast self-assemble from various building blocks on the surface of the coacervates and provide the protocells with physical and chemical stability, surface modifiability and high biocompatibility.…”
Section: Llps Droplet Stabilization Strategiesmentioning
confidence: 99%
“…This requires the rationale design of coating ligand/substrate for good nanoscale recognitions on scaffolds ( e.g. , NP, 341,353 antibody, 354 polymer, 355,356 biocondensate 357–359 ), including optimized accessibility, homogeneity, orientation, and functionality. For example, Ulijn et al demonstrated that enzymatic unveiling of surface-bound zwitterionic tetrapeptides through MMP-9 can activate the self-assembly of AuNPs.…”
Section: Activatable Colorimetric Systemsmentioning
confidence: 99%